Indonesian Infotainment in the Perspective of Islamic Law - Muhammad Ikhsan; Azwar Iskandar (JURNAL INDO-ISLAMIKA, 2021)
This study aims to provide an overview of the nature of infotainment, the view of Islamic law on media and information products, and the view of Islamic law on infotainment. This research is a qualitative, descriptive study with library research techniques using philosophical, historical, and sociological approaches. The results show two main findings. First, infotainment is basically an information product containing entertainment elements, news, and information about celebrities. It is dominated by celebrity news that is not required by society and potentially provides negative impacts on people's social lives. Second, in the perspective of Islamic law, the media of information in all its forms is something of a neutral nature and hence the legal status depends on the usage purpose. By looking at the elements contained in an infotainment show (gibah, namīmah, and al-jahr bi al-fahisyah) coupled with the violation of at least two main objectives of Islamic Sharia (hifz al-a'rad and hifz al -'aql), infotainment with its present reality is something that is forbidden. The implication of this conclusion is that all attempts to produce, distribute, and consume them are unlawful (haram).